Powerful knowledge? A multidimensional ethical competence through a multitude of narratives - Osbeck, Christina (HTS teologiese studies, 2020)
High-quality education has been considered important for social justice, although what good education means is contested. A project aimed at identifying varieties of conceptions of ethical competence (EthiCo) was presented as well as another that focused on a fiction-based approach to ethics education (EE). A multidimensional ethical competence mediated through a multitude of narratives was shown as a strong contribution to EE. The aim was to discuss as to what extent such a multidimensional ethical competence mediated through a multitude of narratives could be understood as powerful knowledge. Sweden, where national tests lately have been understood as a tool to increase achievements, but where an unclear understanding of desired knowledge in EE exists, was the setting. Methodologically, the article drew on Michael Young’s definition of powerful knowledge, a hermeneutic meta-study on the findings of EthiCo concerning conceptions of ethical competence, as well as Mark Tappan’s sociocultural perspective on moral development. These perspectives were brought together to discuss powerful knowledge in EE as a contribution to education for social justice. Whether a multidimensional ethical competence mediated through a multitude of narratives could be understood as powerful knowledge was shown to be dependent on the definition. Whilst Young’s powerful knowledge is restricted to an academic language, Tappan stresses vernacular language as characteristic for a functional moral discourse. One conclusion was the centrality of fiction in EE for the development of moral discourses that transcend reality and shape ‘knowledge of possibilities’ – powerful in the shaping of societal justice.